The use of miswak (Salvadora persica L.) extract to increase immune response of common carp (Cyprinus carpio L.) in cage - HENNI SYAWAL; SYAFRIADIMAN SYAFRIADIMAN; SYAUQI HIDAYAH (Society for Indonesian Biodiversity, 2008)
The aim of this research was to increase immune response of common carp (Cyprinus carpio L.) in cage to microbial infection and environmental change. This research used completed randomized (RAL) one factor, four treatments and each of three replicates. This treatment was immersion extract miswak (Salvadora persica L.) dose 0, 4.5, 9, and 13.5 g/L. The cage 1 x 1 x 1.2 m, with density 50 fish/ cage (average initially 10-15 cm). Immersion was done once time a week along three weeks, l0 min, and after it fish reared in cage along 30 days. The response parameters assayed were survival rate, haematocrit, erythrocytes, leukocytes, and water quality. The results of experiment showed that the dose optimum 9 mg/L (P2) with survival rate 99.66% and P0 (70.66%). The level of haemotocrit was 18.93-34.36%, erythrocytes 3.597.000-6.112.000 cells/mL3, leukocytes 24.748-143.070 cells/mL3. It was concluded, which miswak extract at a dosage 9 mg/L can increase survival rate and immune response of common carp.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: Salvadora persica L., Cyprinus carpio L., haematology.